2021
DOI: 10.1016/j.eclinm.2021.100938
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use disorder and health service utilization among COVID-19 patients in the US: A nationwide cohort from the Cerner Real-World Data

Abstract: Background: Both opioid use and COVID-19 affect respiratory and pulmonary health, potentially putting individuals with opioid use disorders (OUD) at risk for complications from COVID-19. We examine the relationship between OUD and subsequent hospitalization, length of stay, risk for invasive ventilator dependence (IVD), and COVID-19 mortality. Methods: Multivariable logistic and exponential regression models using electronic health records data from the Cerner COVID-19 De-Identified Data Cohort from January th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 31 publications
(42 reference statements)
6
40
2
Order By: Relevance
“…A full text review of the remaining 52 studies was then conducted, and 47 records were eliminated since they were reviews, abstract, letters, conferences, without comparison between opioid use and no-opioid use, or without clinical outcomes reported. Therefore, a total of 5 studies with 1,023,224 patients were included in the final analysis [ [22] , [23] , [24] , [25] , [26] ]. The process of study retrieval is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A full text review of the remaining 52 studies was then conducted, and 47 records were eliminated since they were reviews, abstract, letters, conferences, without comparison between opioid use and no-opioid use, or without clinical outcomes reported. Therefore, a total of 5 studies with 1,023,224 patients were included in the final analysis [ [22] , [23] , [24] , [25] , [26] ]. The process of study retrieval is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Study Region Opioid No opioid Study design Sample size Definition of opioid Adjusted variables NOS score Age Male (%) Age Male (%) Allen [ 22 ] 2020 U.S.A NR NR NR NR Retrospective cohort 11,830 ICD-10 codes F11 (opioid use disorder) Sex, age, race and comorbidity 8 Oh [ 23 ] 2021 South Korea NR NR NR NR Retrospective cohort 7713 All opiates except codeine, dihydrocodeine, hydrocodone, and tramadol. Sex, age, race, annual income level in 2020 and comorbidity 8 Qeadan [ 24 ] 2021 U.S.A 60 (48–70) 502 (49.6) 53 (35–68) 25,298 (49.3) Retrospective cohort 52,312 Measured by past opioid overdose or opioid use disorders recorded in ICD-9 or ICD-10 codes Age, gender, race/ethnicity, insurance, region, diabetes mellitus, asthma, hypertension, hydroxychloroquine, remdesivir, decadron or prednisone, aspirin and plavix 8 Tuan [ 25 ] 2021 U.S.A 52.1 ± 17.1 3764 (39.4) 43.1 ± 17.6 199,947 (48.9) Retrospective cohort 418,216 Individuals are prescribed with opioids in three or more consecutive months or at least 90 days at outpatient settings. Age, sex, race/ethnicity and comorbidities (diabetes, essential hypertension, chronic pulmonary conditions, cardiovascular diseases, mental health disorders) 8 Wiener [ 26 ] 2021 U.S.A 71.8 ± 6.3 3382 (45.1) 74.1 ± 7.3 245,186 (46.9) Retrospective cohort 533,153 The unhealthf...…”
Section: Resultsmentioning
confidence: 99%
“…We conducted one of the first nationally representative studies focused on associations between SUD and COVID-19 experiences in the U.S. We found that individuals with a SUD had decreased odds of having access to paid sick leave and increased odds of being laid off from work due to the pandemic. Recent studies have found that individuals with an SUD were at increased risk for contracting COVID-19, and among those who contract COVID-19, those with SUDs have worse outcomes including higher risk of hospitalization and death [ 4 , 5 ]. The present study highlights important non-clinical impacts of the pandemic affecting individuals with SUD and point to structural inequities that can amplify the effects of the pandemic in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Our covariates were selected a priori based on their association with COVID-19 and SUDs: gender [men/women], age [continuous], geographic region [Northeast, South, Southwest, West], and annual household income [<$40,000; $40,000-$99,999; $100,000+]. We also included insurance status [Employer-based, Government (Medicare/Medicaid/Veterans Health Administration) or marketplace, Other, or None] based on recent findings that the relationship between having an opioid use disorder and COVID-19 related outcomes varied by insurance status [ 4 ]. These items were modified versions of questions used in the American Community Survey or America National Election Studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation